Monitoring production process of cisplatin‐loaded PLGA nanoparticles by FT‐IR microspectroscopy and univariate data analysis. Issue 3 (23rd August 2014) - Portaccio, Marianna; Menale, Ciro; Diano, Nadia; Serri, Carla; Mita, Damiano G.; Lepore, Maria
ABSTRACT Cisplatin‐loaded PLGA nanoparticles for drug delivery have been prepared using a well‐established water/oil/water double emulsion‐solvent evaporation method. The production process has been monitored by using Fourier Transform Infrared (FT‐IR) microspectroscopy without using KBr tablets and any preliminary sample preparation. Significant spectra have been obtained for all chemical compounds and for samples at different steps of production process. The use of a linear or univariate approach using a R2 determination coefficient has been proposed for discriminating among FT‐IR spectra even when small differences are present. The obtained results confirm that new geometries of data acquisition contribute to make infrared microspectroscopy a very useful tool for a rapid and detailed monitoring of production processes of pharmacological interest. Moreover, morphological and physiological characterizations have been performed on cisplatin‐loded samples showing results in good agreement with those reported in literature. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41305.